Examining the relationship between migration and land cover change in rural U.S.: evidence from Ohio, United States, between 2008 and 2016. Issue 1 (2nd January 2022) - Park, Sohyun; Chapman, Rebecca; Munroe, Darla K.
ABSTRACT: Rural migration is an integral component of land systems, altering land management both at the origin and destination of migration in regions of Europe and North America. We examine population moving in and out of rural areas in Ohio, U.S.A, between 2008 and 2016 and examine spatiotemporal patterns in land cover. Among families changing residential location, one-third of all household moving events are migration from or to rural areas. A PCA ordination and cluster analysis of rural migration revealed qualitatively distinct patterns. Urban peripheries grew due to in-migration from metro suburban areas, while agricultural and forested areas reflect intra-rural and micropolitan migration. Forested communities have lost population to other rural areas, and rural poverty pockets have gained low-income families from both rural and metro urban areas. Spatial analysis of rural migration patterns and associations with land use helps develop targeted land management strategies and reveals under-represented dynamics in prior studies.